Gestión administrativa y su incidencia en la rentabilidad de la empresa Prodeuteq-ep área Procombise, del cantón Quevedo, periodo 2023-2024. - Santillán Ramírez, Karen Belén (2025)
The company PRODEUTEQ-EP, located in the city of Quevedo, in the province of Los Ríos, operates in various business areas such as PROCOMBISE, ESCUTEQ, CECAPRO, and SOLUTEQ. Among these, PROCOMBISE stands out as the strongest unit, dedicated to the production and commercialization of goods and services. However, profitability evaluation within PRODEUTEQ-EP is carried out in a generalized manner, without considering the individual performance of each unit. This limits a true understanding of PROCOMBISE’s financial performance and hinders well-founded strategic decision-making.